Copy competitively-tested adaptations of wild species, maybe, but not natural ecosystems tested only by persistence. (March 2022) - Denison, R Ford
Some aspects of nature are better potential models for agriculture than others. Natural ecosystems have not competed against each other the way wild plants have, so individual adaptations have been improved more consistently over time, relative to ecosystem-level patterns and processes. Wild plants have also been improved by competitive natural selection for longer than humans or most ecosystems have existed. Evolution-tested adaptations, like inducible defenses against pests, will often be worth preserving (if inherited by crops from wild ancestors) or copying. However, when there are tradeoffs between individual competitiveness and plant-community performance, as illustrated by solar tracking, reversing effects of past natural selection will often be a better option. Nitrogen-fixing cereals are unlikely to be a viable alternative to fertilizer unless we can copy adaptations that existing nitrogen-fixing plants have evolved to deal with oxygen and with conflicts of interest with symbionts.